Profit Sharing System for Fishermen Using Bubu Fishing Gear on Barrang Lompo Island, Sangkarrang District, Makassar City - Merselindah, Lisa; Adhawati, Sri Suro; Baso, Aris; Made, Sutinah; Gosari, Benny Audy Jaya (PONGGAWA : Journal of Fisheries Socio-Economic, 2025)
Most residents of Barrang Lompo Island work as traditional fishermen who rely on fish capture activities using bubu traps. The working relationship between gear owners (punggawa) and field workers (sawi) follows a hereditary profit-sharing system that lacks standardized regulations. This study aims to analyze the income and profit-sharing system of bubu trap fishermen. A descriptive quantitative and qualitative method was applied, with data collected through observation, interviews, and questionnaires. The sample consisted of 23 fishing units selected through a census method. The results showed that fishermen’s income varied by season, with the highest income during peak season at IDR 49,790,841 and the lowest during the off-season at IDR 24,858,667 per month. The applied profit-sharing system allocates 40% of the earnings to the punggawa and 60% to the sawi. However, the current system remains verbal and has not yet guaranteed optimal welfare for the labor fishermen. Therefore, regulations and supervision are necessary to ensure a fairer and more sustainable system.